Pengaruh Tingkat Pendidikan, Pengalaman Kerja, Gaji dan Komitmen Organisasi Terhadap Kinerja Pengelola Keuangan Pemerintah Daerah Kabupaten Lebong - Marlia Harahap; Abdullah Abdullah (Faculty of Economics and Business, Universitas Malikussaleh, 2016)
This study aims to provide empirical evidence about the effect of the level of education, work experience, salary and commitment to the organization’s financial management performance.Sample in this study is the civil servants who work in the financial section in the units of Lebong District, totaling 90 peoples. This study uses multiple regression analysis. The results showed that the level of education and salary not a positive influence on the performance of financial management while work experience and organizational commitment has a positive effect on the performance of financial management. The results of this study are expected to be taken into consideration for the Local Government District Regional Head Lebong so much attentionto the importance of work experience and organizational commitment affecting the financial managementperformance.Keywords: Level of Education, Work Experience, Salary, Organizational Commitment, Financial Management Performance